Safety and Efficacy of Revision Minimally Invasive Lumbar Decompression in the Ambulatory Setting. Issue 8 (15th April 2019) - Hirsch, Brandon P.; Khechen, Benjamin; Patel, Dil V.; Cardinal, Kaitlyn L.; Guntin, Jordan A.; Singh, Kern
Abstract : Study Design: A retrospective analysis. Objective: The aim of this study was to investigate differences in perioperative outcomes between patients undergoing revision minimally invasive lumbar spine decompression (MIS LD) in the ambulatory and hospital-based surgical settings. Summary of Background Data: Revision LD has been associated with an increased risk of complications compared with primary LD. Furthermore, ambulatory primary LD has been demonstrated to be a safe and viable option in appropriately selected patients. However, there is a paucity of information comparing hospital-based versus ambulatory outcomes in revision LD. Methods: A prospectively maintained surgical registry of patients undergoing revision MIS lumbar laminectomy and/or discectomy for degenerative pathology from 2013 to 2017 was retrospectively reviewed. Propensity score matching was performed to adjust for measured confounding variables, including patient age, comorbidity burden as measured by Charlson Comorbidity Index, and preoperative diagnosis. Differences in operative variables, complication rates, pain scores, narcotics consumption, and reoperation rates were assessed using Pearson Chi-squared analysis (categorical) and Student t test (continuous). Results: Seventy patients were included, of whom 35 underwent revision MIS LD at a hospital-based center (HBC), and 35 underwent surgery at an ambulatory surgical center (ASC). HBC and ASC patients demonstrated similar postoperative visual analog scale pain scores and hourly narcotics consumption during surgical stay ( P < 0.001). ASC patients exhibited a significantly shorter length of stay than hospital-based patients (2.7 vs . 11.6 hours, P < 0.001). Conclusion: Patients undergoing revision MIS LD in an ASC demonstrated similar perioperative outcomes as compared to patients undergoing revision MIS LD in a HBC. These results suggest that revision MIS LD can be performed safe and effectively in the ambulatory setting in an appropriately selected surgical population. Further study of patient outcomes following spine surgery performed outside of the traditional hospital setting is crucial, as the delivery of care in the ambulatory setting continues to grow in popularity. Level of Evidence: 3 Abstract : This study compares outcomes in patients who underwent a revision minimally invasive lumbar decompression (MIS LD) in an ambulatory surgery or hospital-based center. The results demonstrate that revision MIS LD can be safe and effectively performed in either setting.